POHON CITA-CITA: IMPLEMENTASI GERAKAN âSISDARLINGâ BERBASIS PENDIDIKAN KARAKTER - Nurul Majid, Dewi Yulia; Kurnia S, Ayu (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Character education is important, because it contains good moral values and be able to help children understand themselves, put themselves in a social environment and be able to support in academic achievement and non-academic. The one way to implement is sisdarling movement. Sisdarling stands for Environmentally Conscious Student that contains character education to foster positive character that focuses on the 7 characters, including: (1) love the environment; (2) Berke deity; (3) is responsible; (4) creative; (5) cooperate; (6) to be honest; (7) optimistic. The object of this program are children kelas3, 4, and 5 SD puppetry 03, Banyumanik-City Semarang.Pohon Ideals has the goal of foster positive characters to instill environmental awareness since early. Stages of implementation consists of four stages, namely the stage of program targets, dissemination, implementation and evaluation. The method used for the implementation of the program is Edufun (Education in Fun Learning).